Healthcare Providers' Perceptions of Single-Room Versus Traditional Maternity Models: A Concurrent Mixed-Methods Study. Issue 4 (October 2019) - Hall, Marc; Nowell, Lorelli; Castrogiovanni, Nina; Palacios-Derflingher, Luz; Norris, Jill M.; White, Deborah E.
Abstract : While many hospitals have transitioned from traditional maternity care to a single-room maternity model, little is known about how healthcare providers' practice differs between the models. This mixed-methods study compared healthcare providers' job satisfaction and team collaboration between traditional and single-room maternity care and explored how each model shaped providers' practice. Data were collected via questionnaires and interviews with healthcare providers from 2 hospitals. Independent t tests, Mann-Whitney U tests, and thematic analysis were used in analysis; findings were then triangulated. No difference was found in team collaboration and job satisfaction scores between single-room ( n = 84) and traditional ( n = 42) maternity care; however, providers described different means toward satisfaction and collaboration in the interviews ( n = 18). Single-room maternity care providers valued interprofessional teamwork, patient/family involvement, and continuity of care. Traditional maternity care providers enjoyed specialization but described teamwork as uniprofessional and disconnected across professions; transfers between units weakened communication and fragmented care. While single-room maternity care providers described less tension and a more holistic patient-family journey, further research must be undertaken to examine whether and how interprofessional collaboration and communication impact patient and health system outcomes.